Bio-cementations: A Review on Enzyme and Microbially Induced Calcite Precipitation Mechanisms and Applications in Geotechnical Engineering (Journal of Engineering, 2024)
Modern methods to improve soil must deal with sustainable and green building purposes, and precipitated calcite is the most modern bio-cementation method to improve soil sustainably. Enzyme-induced calcite precipitation and microbially-induced calcite precipitation are precipitated calcite's best branches in bio-cemented soil improvement. EICP and MICP contain calcium chloride, urea, water, urease enzyme and other chemical materials (for MICP As nutrients for bacteria) that are mixed together to precipitate calcium carbonate in the soil. The precipitated calcium carbonate was worked as a binder between soil particles, filling the void and improving the soil's properties. By utilizing this technique in the field, several researchers were able to achieve favorable outcomes in the areas of soil improvement and other engineering applications, including concrete repair and other applications, while also taking into consideration the objectives of sustainability. treatment carried out on soils with one or many cycles of the treatment solution. The treatment revealed a significant improvement in the value of unconfined compression strength, compared to untreated soils. During certain experiments, the unconfined compression strength revealed that soils treated with the enzyme approach exhibited higher values compared to soils treated with a mixture containing a certain proportion of regular Portland cement. The encouraging outcomes that were achieved through the utilization of this test in both the laboratory and the field can be utilized in large-scale operations. Till now, this method has been considered under study. In Iraq there are no any research in term of EICP treatment while there are several research about using MICP in soil treatment.